Design and Modelling of Innovative Propulsion Layouts with Pivoted Thrusters For Underwater Vehicles. Issue 21 (2016) - Allotta, Benedetto; Pagliai, Marco; Pugi, Luca
Abstract: Autonomy, performances and manoeuvrability of underwater vehicles are deeply influenced by the features of their propulsion layouts. In particular, the manoeuvrability and the reliability are very important requirements for ROV (Remotely Operated Vehicle) and AUV (Autonomous Underwater Vehicle), for this reason it is necessary to improve these features for underwater vehicles especially if they are emploied in shallow water or potentially dangerous environments. In this work are introduced an application of reconfigurable and redundant propulsion system.